2020
DOI: 10.3390/en13030652
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cold Pressing Process Parameters of Chopped Corn Straws for Fuel

Abstract: Pressed condensation is a key process before the reclamation of loose corn straws. In this study, the effects of stabilization time on the relaxation density and dimensional stability of corn straws were studied firstly, and then the stabilization time was determined to be 60 s by comprehensively considering the compression effect, energy consumption, efficiency and significance. On this basis, the effects of the water content (12%, 15%, 18%), ratio of pressure maintenance time to stabilization time (0, 0.5, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In conclusion, the soybean dregs can enhance the bonding between corn stover particles and improve the relaxed density of the formed pellets. However, when the moisture content in materials exceeded a certain level, the relaxed density of the pellets decreases [ 16 ], which also explains why the relaxed density declines after the addition of fermented soybean dregs was above a certain level. Compared with the feed pellets from the corn stover of 4 mm, the relaxed density of formed pellets from corn stover of 2 mm was larger, and the difference between the two became smaller when the addition–mass ratio of fermented soybean dregs increased (>5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the soybean dregs can enhance the bonding between corn stover particles and improve the relaxed density of the formed pellets. However, when the moisture content in materials exceeded a certain level, the relaxed density of the pellets decreases [ 16 ], which also explains why the relaxed density declines after the addition of fermented soybean dregs was above a certain level. Compared with the feed pellets from the corn stover of 4 mm, the relaxed density of formed pellets from corn stover of 2 mm was larger, and the difference between the two became smaller when the addition–mass ratio of fermented soybean dregs increased (>5%).…”
Section: Resultsmentioning
confidence: 99%
“…In the water content range of 8–24% for corn stover powder under mesh of 16–100, the relaxation density of the formed pellets decreased with an increase in water content [ 15 ]. The optimal forming moisture content was 13.63% for chopped corn stover [ 16 ]. The forming experiments of unbundled corn stover showed that the relaxed density of straw briquette increased first and then dropped with the increase in moisture content, and the optimal moisture content was 15% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen from the scatter plot that the actual values were basically distributed on the predicted curve, consistent with the trend of the predicted values, and linearly distributed. The predicted precision of the models was 15.72 and 23.61, which was far larger than four, suggesting the models were precise [35].…”
Section: Anova Analysismentioning
confidence: 87%
“…The data of the experiment were analyzed by using the analysis of variance (ANOVA) and least-significant difference (LSD) at the significance levels of 0.01 and 0.05 in Origin 8.0 software [34,35]. The Design-Expert software was employed to generate response surfaces and conduct multi-objective optimization.…”
Section: Discussionmentioning
confidence: 99%
“…The first part is the optimization of the processing parameters. Based on such research, it has been found that proper ranges of parameters, such as moisture content, particle size, and compression rate, could lead to low energy consumption and high pellet quality (Niccolò et al 2018;Chen et al 2019). However, the optimal ranges vary for different biomass materials (Whittaker and Shield 2017).…”
Section: Introductionmentioning
confidence: 99%